ECONOMIC ENVIRONMENT AND SMALL AND MEDIUM ENTERPRISES IN NIGERIA A STUDY OF SELECTED SMES IN AKURE, ONDO STATE - Olufunmilayo Arinola, Akindowo; Ifedayo Ade, Olorunfemi (International Journal of Innovations in Engineering Research and Technology, 2023)
This research work examined the effect of economic environment on small and medium enterprises in Nigeria. The study has become imperative because of the slow progress small and medium Enterprises have made as instruments of economic growth and development. This study focused its empirical verification on economic environmental variables, which is inflation rate. Data were collected using primary and secondary data. Regression Analysis techniques were used to describe and analyse the results from the field. The obtained results showed that inflation rate have significant effect on the operations of SMEs indicated by its t value and p value shown in parenthesis: inflation rate (t = 3.195; P < 0.05).. Hence, it is recommended that Federal Government should concentrate on modifying existing economic policies and regulatory framework to ensure stability in inflation rates.